2019
DOI: 10.15211/soveurope620194047
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Policy Choice of the Political Elites of the Baltic States: Opportunities and Limitations of the Institutional Regionalism

Abstract: Аннотация. Статья посвящена проблеме поиска объяснительной модели внешнеполитического выбора политических элит стран Прибалтики. Цель настоящего исследования заключается в сопоставлении новейших теоретико-методологических наработок с актуальными практиками поведения прибалтийских государств на международной арене. В качестве опорных концепций привлечены теории малых государств, убежища (укрытия) в контексте институционального регионализма. Общность элитного выбора внешнеполитической ниши обусловлена относитель… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…134] 19. Tarasov, while examining the Latvian example, suggested that the ethnic policy was aimed at forming a new identity for Russians in Latvia -"Eurorussians" or "Latvians" [based on the Nation of Latvia, rather than the Latvian ethnicity -translator's note] in the long term, and this had nothing to do with the formation of a united civic nation[31].…”
mentioning
confidence: 99%
“…134] 19. Tarasov, while examining the Latvian example, suggested that the ethnic policy was aimed at forming a new identity for Russians in Latvia -"Eurorussians" or "Latvians" [based on the Nation of Latvia, rather than the Latvian ethnicity -translator's note] in the long term, and this had nothing to do with the formation of a united civic nation[31].…”
mentioning
confidence: 99%